Manajemen Mutu Pendidikan melalui Analisis SWOT - Alifianti Uswatun Hasanah; Sita Ratnaningsih; Maftuhah Maftuhah; Zahruddin Zahruddin; Iwan Purwanto (Journal on Education, 2024)
Education is a crucial element in everyday life, playing an essential part in the cognitive, affective, and psychomotor development of individuals. Improving the quality of education continues to evolve, especially through the management of educational institutions. One effective method in strategic planning to improve the quality of education is SWOT analysis. SWOT analysis identifies strengths, weaknesses, opportunities, and threats in an organization, helping to formulate strategies that maximize strengths and opportunities and minimize weaknesses and threats. This research uses a qualitative approach with a literature study method to examine the relevance of SWOT analysis in improving the quality of education. The study results show that SWOT analysis provides a comprehensive picture of the internal and external conditions of educational institutions, helps create a vision of the future, and develops relevant and innovative programs. Thus, the application of SWOT analysis in strategic planning can improve the overall quality of education, through identifying and utilizing strengths and opportunities as well as managing weaknesses and threats.